2012
DOI: 10.3109/08990220.2012.725680
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and neurophysiological mechanisms related to postural control and efficiency of movement: A review

Abstract: Understanding postural control requires considering various mechanisms underlying a person's ability to stand, to walk, and to interact with the environment safely and efficiently. The purpose of this paper is to summarize the functional relation between biomechanical and neurophysiological perspectives related to postural control in both standing and walking based on movement efficiency. Evidence related to the biomechanical and neurophysiological mechanisms is explored as well as the role of proprioceptive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 175 publications
0
68
0
1
Order By: Relevance
“…In the correlation analysis, PIGD score was significantly and negatively correlated with MoCA score (Table 3), which was consistent with the hypothesis that cognitive impairment might be associated with the PIGD subtype. Postural control is referred to the control of the body’s position with the aim of maintenance of balance and orientation3334. A previous study showed that more cognition-related regions, such as caudate, fusiform gyrus and inferior parietal lobes35, were affected in PIGD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the correlation analysis, PIGD score was significantly and negatively correlated with MoCA score (Table 3), which was consistent with the hypothesis that cognitive impairment might be associated with the PIGD subtype. Postural control is referred to the control of the body’s position with the aim of maintenance of balance and orientation3334. A previous study showed that more cognition-related regions, such as caudate, fusiform gyrus and inferior parietal lobes35, were affected in PIGD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Balance is a multi-dimensional motor skill whose nuances can be recorded by means of motor test procedures or instrumental methods15 ) . In our study, postural sway was analyzed as a reliable parameter26 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Body posture is a complex controlled process that is influenced by a number of biomechanical and neurophysiological mechanisms15 ) . Postural control includes the alignment of body segments through muscular activity26 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subject literature assumes that COP oscillations correspond to the degree of balance. The most frequently analysed parameter is the length of the path designated by the movement of the COP of the feet [9][10][11][12]. Dynamic balance tests use measurement devices with an unstable surface.…”
Section: Introductionmentioning
confidence: 99%